Kunst in kwartier 1998 : Kwartet : kunst en kind. (Arnhem : Stichting 6828 KK, Kunst in kwartier, 1998)
Andrew, Eve ; Askjaer Veldt, Marion ; van den Beukel, Adri ; Bosman, Josje ; Bouwsma, Bart ; Dekkers, Jozef ; Gerrits, Kassiël ; Grote Beverborg, Ellen ; Herfkens, W. ; van Kleef, Anja ; Loman, Lex ; Nijman, Martin ; Noordeman, Arjen ; van Oosten, Rob ; Overbeek, Madelon ; Peek, Esther ; Peters, Hans Christiaan ; Peyer, Ton ; Phillipsen, Gérard ; Pluygers, Pieter ; Postma, Marijke ; Roelofs, Iris ; Strik, Maria ; Sueters, José ; Veerman, Rob ; Verstegen, Jolanda ; Vis, Ewout ; Wezenberg, Johan ; Wesseling, Laurens ; de Wit,Marta ; Wittenberg, Esther ; Zeilstra, Agnes
Kunst in kwartier 1998 : Kwartet : kunst en kind, Gemeente Arnhem, 1998
Nederlands
kunstcatalogus